Bioprocessing of soybeans (Glycine max L.) by solid-state fermentation with Eurotium cristatum YL-1 improves total phenolic content, isoflavone aglycones, and antioxidant activity. Issue 29 (30th April 2020) - Chen, Yulian; Wang, Yuanliang; Chen, Jiaxu; Tang, Hao; Wang, Chuanhua; Li, Zongjun; Xiao, Yu
Abstract : Solid-state bioprocessing with Eurotium cristatum is an effective approach for the enhancement of total phenolic content, isoflavone aglycones, and antioxidant activity of soybeans. Abstract : In this study, soybean ( Glycine max L.) was bioprocessed with fungal strain Eurotium cristatum YL-1 by using the solid-state fermentation (SSF) technique. The effect of SSF on total phenolic content (TPC), isoflavone compositions, and antioxidant activity of soybean during different fermentation periods was evaluated. Results showed that TPC and isoflavone aglycones were significantly increased, whereas glucoside isoflavones were remarkably reduced during SSF. After 15 days of SSF, the TPC, daidzein, genistein, and total aglycones of soybeans were approximately 1.9-, 10.4-, 8.4-, and 9.4-fold higher, respectively, than those of non-fermented soybeans. During SSF, β-glucosidase activity was very high, whereas α-amylase and protease activities were at moderate levels, and cellulase activity was relatively low. A highly positive correlation was found between TPC and the activities of α-amylase (correlation coefficient R 2 = 0.9452), β-glucosidase ( R 2 = 0.9559), cellulase ( R 2 = 0.9783), and protease ( R 2 = 0.6785). Linear analysis validated that the β-glucosidase produced by E. cristatum contributed to the bioconversion of soybean isoflavone glucosides into their aglycone forms. The DPPH radical and ABTS˙ + scavenging activity, reducing power, and ferric reducing antioxidant power of soybeans were considerably enhanced during SSF. Principal component analysis and Pearson's correlation analysis verified that the improvement in TPC and isoflavone aglycone content during SSF was mainly responsible for the improved antioxidant capacity of soybeans. Thus, our results demonstrated that solid-state bioprocessing with E. cristatum is an effective approach for the enhancement of the TPC, isoflavone aglycones, and antioxidant capacity of soybeans. Bioprocessed soybean products might be a healthy food supplement rich in antioxidants compared with non-fermented soybean and thus could be a source of natural antioxidants.